Perancangan Sistem Informasi Bilmo Order Management Pada PT Bilmo Global Utama - Hesti Wiraatmaja; Isnan Mulia; Edi Nurachmad; Marwan Effendy (Jurnal Informatika Kesatuan, 2025)
Information systems play primary role in an organization. By having an information system, organizations or companies can ensure high-quality information and make quick, accurate, dan precise decisions. An integrated information system will make the performance of an organization or company more systematic and directed. However, many companies have not successfully utilized this technology effectively in their data and information management processes. PT. Bilmo Global Utama is a company engaged in web creation services, web design, graphic design, digital marketing with GoogleAds, and social media content design. Currently, the business processes at PT. Bilmo Global Utama are still manual, making them inefficient and prone to errors. This study aims to design and implement an information system that can facilitate the order process, provide the complete information, and generate transaction reports. This research was conducted using the SDLC (Software Development Life Cycle) approach with the Agile model. Data were collected through interviews, observations, and literature studies. The result of this study indicate that designed systems covers the business processes from initial ordering to website completion. Thus, the system successfully addresses the manual business process issues faced by PT. Bilmo Global Utama. The implementation of the bilmo order management information system has several advantages for the company, including : Increased efficiency, Better monitoring, Easier report generation, and Minimizing manual errors. System testing included functionality testing, performance testing, and user acceptance testing (UAT). Functionality testing showed that all system features work well as expected. Meanwhile, performance testing indicated a good average skor of 96,75. User acceptance testing (UAT) yield a satisfactory score of 88%.